THE AEROBIC EXERCISE INCREASES COGNITIVE FUNCTION BIOMARKER, KLOTHO PROTEIN, IN ALZHEIMER DISEASE - Arrianti, Emilia Eka; Natalia, Fransisca; Ayu, Melisa; Afida, Kaisa Lana; Shine, Lina Meylyn; Wahyuni, Nila; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 10 No 2 (2022): Volume 10, No. 2, May 2022, 2022)
Aging is an inevitable process in human. It causes deterioration of many organs in human bodies such as the brain. The most common pathological aging condition in the brain is Alzheimer’s disease. This disease is the leading cause of deficits in short term memory, praxis, visuospatial, and executive function. It can impair cognitive function in older adults. A lot of intervention has been studied to treat Alzheimer’s disease. One of them is the aerobic exercise. Some studies find aerobic exercise increases the anti-aging protein, klotho protein. Klotho is a systemic-biomarkers that has an important role in sustaining cognitive function and brain integrity.  The level of plasma klotho protein is increased by doing aerobic exercise moderately for 12 weeks. The increase of klotho protein improves memory formation and hippocampus function. In Alzheimer’s disease, klotho protein has the ability to lower the formation of neurofibrillary tangles. Hence, aerobic exercise is an essential intervention to improve cognitive function in Alzheimer’s disease patient.